2003
DOI: 10.1007/s11842-003-001-y
|View full text |Cite
|
Sign up to set email alerts
|

Sustaining family forests in rural landscapes: Rationale, challenges, and an illustration from oregon, USA

Abstract: Family forests are critical components of rural landscapes, societies and economies. In Oregon, where nonindustrial private forests comprise only 16% of the forestland base, the ecological, social and economic impact of this ownership category is disproportionately large. This is due to the landscape position these lands occupy, the diversification they contribute to forest cover and local economies, and the political and cultural connections they provide to urban populations. The significance of this ownershi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0
1

Year Published

2009
2009
2017
2017

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(8 citation statements)
references
References 9 publications
(6 reference statements)
0
7
0
1
Order By: Relevance
“…Other authors cover parcelization in the general context of the size of forest holding problem. Bliss described the two fundamental shifts leading to parcelization: changes in the structure and pattern of private forest ownerships and changes in the social values of the United States as it changes from rural to urban to suburban [134]. He does define the traditional NIPF problem of poor forest management on family forests, leading to poor forest productivity, and the unpredictable behavior of family forest owners.…”
Section: Parcelizationmentioning
confidence: 99%
“…Other authors cover parcelization in the general context of the size of forest holding problem. Bliss described the two fundamental shifts leading to parcelization: changes in the structure and pattern of private forest ownerships and changes in the social values of the United States as it changes from rural to urban to suburban [134]. He does define the traditional NIPF problem of poor forest management on family forests, leading to poor forest productivity, and the unpredictable behavior of family forest owners.…”
Section: Parcelizationmentioning
confidence: 99%
“…As noted above, scholars in economics, geography, and regional development point to recent employment and revenue declines in extractive economies as concomitant with the ascendance of new economies, therefore, a result of an overall ''rural restructuring'' (Nelson 2001(Nelson , 2002Swanson 2004), entailing the ''obsolescence of former modes of organizing and regulating economic activity'' (Bridge 2000:253) and a decline of primary commodity production (Bridge and Jonas 2002). New institutional arrangements have decoupled forests from manufacturing and facilitated the subdivision of productive land for consumptive (higher and better use) development (Bliss 2003;Erickson and Rinehart 2005). The Greater Yellowstone Ecosystem is a paramount example of the transformation from extractive to servicebased economy (Rasker and Hansen 2000).…”
Section: Is the Old West Really Dead?mentioning
confidence: 99%
“…"Results suggested concern about sprawl among approximately onehalf of the logger respondents in the region, particularly in New Hampshire, where 60% of respondents indicated that there will be less logging in their area in 10 yr because of sprawl." Bliss (2003) argued that family forests are threatened by parcelization and fragmentation at the urban fringe, and this issue is greater than a simple matter of economics or management of a parcel or woodlot. "The role of family forests in the wider context of landscape, culture, and rural economy" warrants attention (Bliss 2003).…”
Section: Introductionmentioning
confidence: 99%
“…Bliss () argued that family forests are threatened by parcelization and fragmentation at the urban fringe, and this issue is greater than a simple matter of economics or management of a parcel or woodlot. “The role of family forests in the wider context of landscape, culture, and rural economy” warrants attention (Bliss ).…”
Section: Introductionmentioning
confidence: 99%